QUANTUM LOCALIZATION AND ENERGY-FLOW IN MANY-DIMENSIONAL FERMI RESONANT SYSTEMS - Logan, D; Wolynes, P (1990)
The quantum mechanics of energy flow in many-dimensional Fermi resonant systems has several connections to the theory of Anderson localization in disordered solids. We argue that in high dimensional and highly quantum mechanical systems the energy flow can be modeled as coherent transport on a locally but weakly correlated random energy surface. This model exhibits a sharp but continuous transition from local to global energy flow characterized by critical exponents. Dephasing smears the transition and an interesting nonmonotonic dependence of energy flow rate on environmental coupling is predicted to occur near the transition. © 1990 American Institute of Physics.